2013
DOI: 10.1158/1078-0432.ccr-13-1116
|View full text |Cite
|
Sign up to set email alerts
|

Lessons Learned from Radiation Oncology Clinical Trials

Abstract: A Workshop entitled “Lessons Learned from Radiation Oncology Trials” was held on December 7–8th, 2011 in Bethesda, MD, to present and discuss some of the recently conducted Radiation Oncology clinical trials with a focus on those that failed to refute the null hypothesis. The objectives of this Workshop were to summarize and examine the questions that these trials provoked, to assess the quality and limitations of the pre-clinical data that supported the hypotheses underlying these trials, and to consider poss… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 73 publications
(71 reference statements)
1
19
0
Order By: Relevance
“…We have therefore initially evaluated a strategy using MMP and cRGD binding integrin targeted ACPP delivery of MMAE in combination with focal IR (17). A major limitation to the therapeutic utility of radiosensitizers is the lack of tumor specific delivery (22, 23). Radiosensitizer delivery that is non-targeted can result in increased radiosensitization of not only tumor cells, but also surrounding normal tissue.…”
Section: Discussionmentioning
confidence: 99%
“…We have therefore initially evaluated a strategy using MMP and cRGD binding integrin targeted ACPP delivery of MMAE in combination with focal IR (17). A major limitation to the therapeutic utility of radiosensitizers is the lack of tumor specific delivery (22, 23). Radiosensitizer delivery that is non-targeted can result in increased radiosensitization of not only tumor cells, but also surrounding normal tissue.…”
Section: Discussionmentioning
confidence: 99%
“…This workshop "Lessons Learned from Radiation Oncology Trials" 42 concluded that preclinical studies must conduct at least in vitro clonogenic assay and contact the Radiation Research Program at the US National Cancer Institute (NCI), which is coordinating the preclinical and clinical studies for multiple targeted agents combined with RT in panels of human cancer cells, before embarking on combinatorial therapies and generate in vivo data using different human cancer xenograft models. Orthotopic models are encouraged.…”
Section: Advances In Mouse Models-how To Fill the "Translational Gap"?mentioning
confidence: 99%
“…Adjuvant hypoxia-modifying treatment has been shown to improve the efficacy of radiotherapy in cervical cancer (6), and combination trials to find the optimal drug have been performed (7,8) and are underway (ClinicalTrials.gov identifier NCT02394652). In many trials, difficulties in detecting drug effects and toxicity are major problems, as patients are randomized to the adjuvant treatment without knowledge of the hypoxia status of the tumor (9). Development of methods for classifying patients according to the hypoxia status is therefore an important requirement for reliable drug evaluation and to avoid added toxicity to patients with no expected benefit.…”
Section: Introductionmentioning
confidence: 99%